Unraveling the Main Chain and Side Chain Effects on Thin Film Morphology and Charge Transport in Quinoidal Conjugated Polymers. (5th June 2018) - Liu, Xuncheng; He, Bo; Garzón‐Ruiz, Andrés; Navarro, Amparo; Chen, Teresa L.; Kolaczkowski, Matthew A.; Feng, Shizhen; Zhang, Lianjie; Anderson, Christopher A.; Chen, Junwu; Liu, Yi
Abstract: Three series of low‐bandgap polymers based on a novel quinoidal para ‐azaquinodimethane ( p ‐AQM) unit are devised and synthesized, enabling an in‐depth study of the impact of structural factors such as polymer main chain, branching point of the side chain, and the length of the branch chains on the thin film morphologies and charge transport properties. Morphological studies reveal that the polymers composed of larger repeating units exhibit a stronger tendency to form edge‐on lamella. On the other hand, altering the side chain structures of polymers with the same main chain configuration indicates that the branching point position has a more deterministic impact than the branch chain length on the interchain interactions and the crystallite orientation. These results demonstrate a compound odd‐even effect of the branching point on the chain packing and morphology, which correlates well with the corresponding field effect transistor performances. The polymer with the branching point at the fourth carbon displays the highest charge carrier mobility over 1.0 cm 2 V −1 s −1, concurrent with a bimodal texture. This study provides a comprehensive description of the correlations between polymer structures, thin film morphology, and device performances, providing a clear path to desirable bimodal thin film texture for charge transport. Abstract : Comparative studies of series of quinoidal polymers with varying main chain or side chain moieties have provided a comprehensive description of the relationship between polymer structures, thin film morphologies, and charge transport properties. A compound "odd‐even" branching point effect is observed experimentally and elucidated theoretically. Such studies provide a unique insight for the future design of high‐performing organic semiconductors.